Serological survey for Leishmania sp. infection in wild animals from the municipality of Maringá, Paraná state, Brazil - EM Voltarelli; SMAA Arraes; Perles; MVC Lonardoni; U Teodoro; TGV Silveira (Journal of Venomous Animals and Toxins including Tropical Diseases, 2009)
Leishmania sp. infection was investigated in wild animals from the Ingá Park, in the municipality of Maringá, Paraná state, Brazil, where American cutaneous leishmaniasis (ACL) is an endemic disease. Sixty-five mammals, comprising Didelphis albiventris, Cerdocyon thous, Lycalopex vetulus, Cebus apella, Dasyprocta azarae, Dasypus novemcinctus, Procyon cancrivorus and Nasua nasua, were captured. Blood samples were collected for parasite cultivation. Antibodies were investigated by direct agglutination test (DAT) using Leishmania (Viannia) braziliensis as antigen. Flagellates were observed in blood cultures of 14 (35.9%) Didelphis albiventris. Anti-Leishmania antibodies were detected in 31 (51.6%) specimens of Cerdocyon thous, Lycalopex vetulus, Cebus apella, Dasyprocta azarae, Procyon cancrivorus and Nasua nasua. These results suggest that Cerdocyon thous and Lycalopex vetulus (crab-eating fox), Cebus apella (capuchin monkey), Dasyprocta azarae (agouti), Procyon cancrivorus (crab-eating raccoon) and Nasua nasua (coati) play an important role in the ACL transmission cycle in the northwestern region of Paraná, Brazil.